The dynamic impact of board composition on CSR practices and their mutual effect on organizational returns - Karim, Sitara; Abdul Manab, Norlida; Ismail, Rusmawati (Emerald Publishing, 2020)
Purpose – The purpose of this paper is twofold. First, it aims to investigate the dynamic impact of board composition (board size, board independence and board diversity) on independent corporate social responsibility (CSR) practices (marketplace, environment, community and workplace). Second, it tends to examine the mutual effect of board composition and CSR practices on organizational returns (return on assets and Tobin’s Q) of 631 Malaysian PLCs listed on Bursa Malaysia during 2006-2017. Design/methodology/approach – The dynamic model (system GMM) provided by Arellano and Bond (1991) and Arellano and Bover (1995) is used for estimations that control for potential dynamic endogeneity, reverse causality, unobserved heterogeneity and simultaneity problems. Findings – Findings reveal weak linkage between board composition and CSR practices where only board diversity is found to be positively linked to marketplace practices of CSR. Further, the mutual impact of board composition and CSR practices on organizational returns suggests board size be positive and board independence to be negative with Tobin’s Q. Board diversity is negative with ROA and positive with Tobin’s Q. Conversely, CSR practices indicate marketplace practices are positive and community practices are negative with Tobin’s Q, environment practices are insignificant with performance, whereas workplace practices are positive with ROA and negative with Tobin’s Q. Practical implications – This research is practically considerable for Bursa Malaysia, Securities Commission Malaysia, policymakers, stakeholders, investors and managers. For academia, the theoretical linkages between agency theory, resource dependence theory, resource-based view and stakeholder theory are highlighted. Moreover, methodological underpinnings are also novel for academicians as well as for practitioners. Originality/value – The paper uncovers multiple aspects: first, it elaborates the dynamic relationship between board composition and CSR practices; second, it examines the combined effect of board composition and CSR practices on company’s accounting and market gains; finally, the study controls for dynamic endogeneity that is the main econometric problem for CG-CSR-performance relationships.